Features of Surgical Treatment of Malignant Tumors of the Heart and Ways to Improve Immediate Results - Andrii R. Vitovskyi; Volodymyr V. Isaіenko; Valentyna M. Ryabytza; Rostyslav M. Vitovskyi (Ukrainian Journal of Cardiovascular Surgery, 2021)
To date, the issues of surgical treatment of malignant cardiac tumors (MCT) remain relevant and are of particular interest to cardiac surgeons. Hospital mortality of this group of patients is extremely high (20–30%). Finding ways to reduce early postoperative mortality remains an extremely important task of oncocardiac surgery.The aim. To analyze the causes of early postoperative mortality based on the data of many years of experience in the surgical treatment of MCT and to propose methods for the prevention of early postoperative complications with the improvement of the immediate results of operations.Materials and methods. From 1970 to 01.01.2021, National Amosov Institute of Cardiovascular Surgery has provided surgical treatment of 67 patients with malignant tumors of the heart which amounted to 7.1% of the total number of observed patients with cardiac tumors (949). Of the 67 patients with MCT, 57 (84.9%) were operated using artificial circulation, three operations (4.6%) were emergency. Hospital mortality was 19.4% (13 patients).Results. Microscopic examination of the removed tumors revealed the presence of necrosis zones, their mechanical damage leads to significant intoxication of the patient. To prevent tumor intoxication (cause of postoperative mortality) in the operative and postoperative periods, new methods of combating such a factor of hospital mortality were used, which helped to improve the results of treatment of MCT. Hospital mortality reduced from 33.3% (1970–2001) to 5.5% (last 10 years), as a result of use these measures.Conclusions. Destruction of the tumor during surgery with artificial circulation leads to the entry of a significant number of tumor cells and toxins into the bloodstream, causing tumor intoxication. Improvement of the immediate results of surgical treatment of MCT depends on their timely diagnosis, which allows for adequate surgery with radical removal of the tumor and the use of detoxification measures, significantly reducing surgical mortality.